ANALISIS STRATEGI PEMASARAN PADA PASAR GLOBAL - Putri Salsa Nabila; Suhairi Suhairi; Irfan Fadhilah (Gapenas Publisher, 2023)
Globalization is a new challenge for companies in implementing marketing strategies. Because with globalization, companies are required to compete with world-class companies that have large capital and higher quality products. Currently, Indonesia is a target market for global companies to enjoy huge profits, while Indonesian companies are losing out in the competition. This study aims to obtain a global marketing strategy in the Indonesian market for Indonesian companies. The research method used is descriptive analysis method. The combination of adaptation of marketing strategy and standard marketing strategy is a global marketing strategy that is in accordance with market conditions in Indonesia